DECOLONIAL NARRATIVES AS A CRITICAL PEDAGOGY PRACTICE IN EFL STUDENTS - Velàsquez, Sara Sofìa Zapata; Gómez, Yuliana Katerine Pulgarín; Cortés, Jose Luis Rodríguez; Guisao, Juan Felipe Arias; Ángel, Edison Ferney Castrillón (Revista Prâksis, 2024)
This paper reflects upon the construction of narratives presented by students of 10th grade from a public institution in the EFL classroom in Colombia. This study was developed using an Action Research method and a sociocritical paradigm to encourage continuous constructions of decolonial narratives among the students. Furthermore, the exploration of narratives shows various significance from economic, social, and cultural perspectives about the role of the language in their context and the influence on their future that stems from their socio-cultural contexts that see English as the only way to success. Finally, the importance of a critical pedagogy approach to critique the reproduction of colonial narratives to develop a broader understanding of English learning.